Metastatic Carcinoma to Percutaneous Endoscopic Gastrostomy Tube Sites: A Report of Five Cases. Issue 4 (1st April 2014) - Zhang, Lanjing; Dean, Stephanie A.; Furth, Emma E.; Weinstein, Gregory S.; LiVolsi, Virginia A.; Montone, Kathleen T.
Abstract: Objective: To characterize the clinicopathologic features of metastatic carcinomas at percutaneous endoscopic gastrostomy (PEG) tube sites. Methods: We reviewed the metastatic malignancies at PEG tube sites (2002–2011). Results: Five patients were identified, each with primary head and neck keratinizing squamous cell carcinoma. The metastases had a mean size of 6.08 cm (95% confidence interval [CI], 3.75–8.41). The time from PEG tube placement to metastasis diagnosis was 9.8 months (95% CI, 6.59–13.01). The survival times from PEG tube placement and from metastasis diagnosis were 23.5 (95% CI, 7.65–39.35) and 13.7 (95% CI, 0–31.08) months, respectively. Compared with a meta-analysis of the largest case series, our male patients were significantly older (mean, 73 years; 95% CI, 62.2–83.9 vs mean 59 years, 95% CI, 56.0–62.0) but had similar survival times. Conclusions: Despite their older ages, our male patients had similar survival times to those reported previously. Larger series are needed to confirm our findings and explore the causes.